Near Miss Obstetric Events and Maternal Death: Experience in Combined Military Hospital, Dhaka - Zaman, Nasrin Ara; Ghani, Khondaker Shahidul; Ruman, Maj Umme (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Obstetric patients can become critically ill for pregnancy related complications other conditions unrelated to pregnancy and may require emergency intensive care. The survival of both the mother and baby depends on the emergency services that are provided at that critical moment. Objective: To evaluate the level of obstetric emergency services in Combined Military Hospital (CMH) Dhaka by comparative analysis of near-misses and mortalities. Materials and Methods: This descriptive cross-sectional study which was conducted by observation of critically ill obstetric patients admitted in general intensive care unit (ICU) of CMH Dhaka from July 2012 to June 2013. Data regarding the disease associated with pregnancy and complications requiring ICU admission or transfer were collected and analyzed to calculate the maternal mortality and near miss ratio. Results: During the study period, 44 cases have been shifted to ICU, representing 2.15% of 2050 deliveries. Haemorrhage (50%) and hypertensive disorder of pregnancy (36.36%) were the two main obstetrical complications requiring ICU management. Surgical intervention was required in 86.3% of cases, 68% required intensive monitoring in ICU followed by blood transfusion in 59% cases. The maternal mortality ratio was 195.12/100000 live birth and fetal mortality rate was 82.2 per 1000 deliveries. Conclusion: By adopting safe motherhood initiative, both morbidity and mortality of pregnant mother can be lowered down. Early diagnosis by assessment, prompt intervention by team of expert obstetricians, intensivist and anaesthetist in reserve ICU can reduce the maternal mortality and morbidity. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 37-40